2008
DOI: 10.1017/s174217050800224x
|View full text |Cite
|
Sign up to set email alerts
|

Soil CO2 respiration: Comparison of chemical titration, CO2 IRGA analysis and the Solvita gel system

Abstract: The measurement of soil carbon dioxide respiration is a means to gauge biological soil fertility. Test methods for respiration employed in the laboratory vary somewhat, and to date the equipment and labor required have somewhat limited more widespread adoption of such methodologies. The purpose of this research is to compare the results of measured soil CO 2 respiration using three methods: (1) titration method; (2) infrared gas analysis (IRGA); and (3) the Solvita gel system for soil CO 2 analysis. We acquire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
99
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(103 citation statements)
references
References 8 publications
2
99
1
1
Order By: Relevance
“…Soil respiration is a reliable and useful indicator of easily decomposable organic C and an important indicator of soil quality and fertility (Haney et al, 2008;Monaco et al, 2008;Iovieno et al, 2009), and there is generally a positive linear relationship between soil respiration and SOC, with R 2 values ranging from 0.35 to 0.70 (Kaiser et al, 1992;Haney et al, 2012;Miller et al, 2014). Iovieno et al (2009) reported an increase in SOC with compost application after 3 yr and found that compost application increased soil respiration from 0.68 mg CO 2 g −1 dry weight h −1 (no compost applied) to 1.18 mg CO 2 g −1 dry weight h −1 when compost was applied at 45 Mg ha −1 yr −1 , reflecting the higher available C pool.…”
mentioning
confidence: 99%
“…Soil respiration is a reliable and useful indicator of easily decomposable organic C and an important indicator of soil quality and fertility (Haney et al, 2008;Monaco et al, 2008;Iovieno et al, 2009), and there is generally a positive linear relationship between soil respiration and SOC, with R 2 values ranging from 0.35 to 0.70 (Kaiser et al, 1992;Haney et al, 2012;Miller et al, 2014). Iovieno et al (2009) reported an increase in SOC with compost application after 3 yr and found that compost application increased soil respiration from 0.68 mg CO 2 g −1 dry weight h −1 (no compost applied) to 1.18 mg CO 2 g −1 dry weight h −1 when compost was applied at 45 Mg ha −1 yr −1 , reflecting the higher available C pool.…”
mentioning
confidence: 99%
“…The culture was maintained by giving continuous lighting and room temperature 25°C for eight weeks. A preliminary test on the amount of carbon dioxide that got into the culture bottle was done in accordance with Haney et al (2008).…”
Section: Plant Materials and Growth Conditionmentioning
confidence: 99%
“…The NH 4 values of the final compost indicated an immature compost in Cyl1 due to high ammonia toxicity and a sufficiently stabilised material in Cyl2. Although the Solvita© test is of a rather qualitative nature, it has been shown to correlate fairly well with other stability tests [47,50,51]. The NH 4 test results result were compatible with the difference in the SS to bulking agent ratio between the two mixtures.…”
Section: Compost Stabilitymentioning
confidence: 63%